2020
DOI: 10.1021/acsptsci.0c00015
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution Profiles of Emtricitabine, Tenofovir, Efavirenz, and Rilpivirine in Murine Tissues Following In Vivo Dosing Correlate with Their Safety Profiles in Humans

Abstract: Emtricitabine (FTC), tenofovir (TFV), efavirenz (EFV), and rilpivirine (RPV) are currently used as components of HIV combination therapy. Although these drugs are widely used in antiretroviral therapy, several organ toxicities related to TFV and EFV have been observed clinically. TFV is associated with nephrotoxicity, whereas EFV-related hepatotoxicity and neurotoxicity have been reported. While the precise molecular mechanisms related to the above-mentioned clinically observed toxicities have yet to be elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Orthogonal technologies such as LC–MS/MS and MALDI-IMS are helpful in characterizing the samples in terms of accurate, sensitive, integrated drug concentrations for PK-PD analyses (LC–MS/MS) and as spatial analyte distribution to understand more nuanced drug localization (MALDI-IMS). To complement traditional LC–MS/MS approaches, imaging mass spectrometry has been applied to visualize ARV drug distribution in a variety of sample types following bolus dosing 70 74 . These studies elegantly showed the usefulness of MALDI-IMS in the context of HIV/AIDS prevention and treatment research.…”
Section: Discussionmentioning
confidence: 99%
“…Orthogonal technologies such as LC–MS/MS and MALDI-IMS are helpful in characterizing the samples in terms of accurate, sensitive, integrated drug concentrations for PK-PD analyses (LC–MS/MS) and as spatial analyte distribution to understand more nuanced drug localization (MALDI-IMS). To complement traditional LC–MS/MS approaches, imaging mass spectrometry has been applied to visualize ARV drug distribution in a variety of sample types following bolus dosing 70 74 . These studies elegantly showed the usefulness of MALDI-IMS in the context of HIV/AIDS prevention and treatment research.…”
Section: Discussionmentioning
confidence: 99%
“…A tissue section is coated with a matrix and a laser is used to ablate ions from small regions for detection by mass spectrometry Imaging of endogenous metabolites as well as parent drugs and drug metabolites within tissues (Seneviratne et al, 2020) Label-free, direct detection of molecules…”
Section: Many Data Processing Programs Availablementioning
confidence: 99%
“…The main ionization techniques used for MSI are matrix-assisted laser desorption/ionization (MALDI), desorption electrospray ionization, laser ablation electrospray ionization, and secondary ion mass spectrometry (SIMS) ( Buchberger et al, 2018 ). Of these ionization techniques, MALDI MSI is the most frequently employed for simultaneous visualization of the spatial distribution of drugs, their metabolites, and endogenous lipid molecules at tissue level ( Prideaux et al, 2010 ; Seneviratne et al, 2018 ; Tang et al, 2019 ; Seneviratne et al, 2020 ). Due to recent improvements in MALDI MS sources, this approach can also be used for single cell imaging.…”
Section: Introductionmentioning
confidence: 99%
“…This new model to study HIV brain infection also aid in the development and testing of new generation ART delivery with improved CNS bioavailability and will be useful for future viral eradication studies. Further, the model now allows studies of newly emerging ART-induced neurotoxicity such as reported for efavirenz [107,108]. However, many laboratory and animal studies have shown a number of direct effects on neuronal and glial function along with pathological outcomes that are linked to amyloid deposition, small vessel damage and aberrations in chemical neurotransmission [109][110][111][112][113][114].…”
Section: Neurohiv and Humanized Micementioning
confidence: 99%